Work Environment and the Bottom Line: Survey of Tools Relating Work Environment to Business Results. Issue 5 (20th October 2011) - Rose, Linda Maria; Orrenius, Ulf Erik; Neumann, Walther Patrick
Abstract Insufficient knowledge of how the working environment (WE) impacts company performance leads to a poor basis for managerial decision making. The objective of this study was to survey and evaluate available tools relating WE to business results. Nine tools were identified and qualitatively evaluated using 11 criteria. The tools were clustered into three categories, ranging from analysis of WE risks as well as calculation of their economic impact to solely investment analysis. Shortcomings in the tools include insufficient attention to quality and productivity issues and insufficient guidance for users. Although further methodological development is indicated, researchers should also attend to the factors affecting tool uptake and application as well as the potential to integrate such analysis into companies' regular accounting systems. © 2011 Wiley Periodicals, Inc.